Opportunities and Potential of Bioenergy Development in Agroindustrial Complexes of Kazakhstan - Omarov, Zhomart; Kalykov, Abay; Niyazbekova, Roza; Yessirkepova, Altyn (International Journal of Energy Economics and Policy, 2021)
The article examines the possibility of developing bioenergy in the agro-industrial complexes of Kazakhstan which can reduce greenhouse gas emissions into the atmosphere and solve problems associated with the disposal of agricultural waste. Special attention is paid to bioenergy generation technologies in agro-industrial complexes which require high capital expenditures to be equipped with modern automation and control facilities. The authors analyse the potential of biogas production from livestock and poultry waste in the agro-industrial complexes of Kazakhstan. During the analysis, it was revealed that the largest volumes of organic waste are produced by cattle breeding, and the smallest – by poultry farming. The article presents an assessment method based on the construction of a two-factor correlation-regression model, in which the effective (endogenous) factor feature is the total production of biogas and the total biomass is selected as an independent (exogenous) factor feature. The results of the calculations showed that the models reflecting the dependence of the total biogas production on the total biomass for cattle, sheep and goats, as well as poultry, correspond to the real flow of processes in the economy and logic. Keywords: Alternative Energy Source, Bioenergy, Green Economics JEL Classifications: Q42, Q50 DOI: https://doi.org/10.32479/ijeep.11530